How can individual differences in autobiographical memory distributions of older adults be explained?. Issue 9 (20th October 2016) - Wolf, Tabea; Zimprich, Daniel
ABSTRACT: The reminiscence bump phenomenon has frequently been reported for the recall of autobiographical memories. The present study complements previous research by examining individual differences in the distribution of word-cued autobiographical memories. More importantly, we introduce predictor variables that might account for individual differences in the mean (location) and the standard deviation (scale) of individual memory distributions. All variables were derived from different theoretical accounts for the reminiscence bump phenomenon. We used a mixed location-scale logitnormal model, to analyse the 4602 autobiographical memories reported by 118 older participants. Results show reliable individual differences in the location and the scale. After controlling for age and gender, individual proportions of first-time experiences and individual proportions of positive memories, as well as the ratings on Openness to new Experiences and Self-Concept Clarity accounted for 29% of individual differences in location and 42% of individual differences in scale of autobiographical memory distributions. Results dovetail with a life-story account for the reminiscence bump which integrates central components of previous accounts.